ANALYSIS OF THE EFFECT OF INFLATION, INTEREST RATE, THE MONEY SUPPLY ON RUPIAH EXCHANGE RATE PERIOD 1996-2014 - Novrida Siregar; Eko Wahyu Nugrahadi (Universitas Negeri Medan, 2019)
The data source is from Bank Indonesia (BI), the result of this research shows that the domestic inflation has a significant positive influence to rupiah exchange rate toword American Dollar, and cash rate ratio has a negative influence to Rupiah exchange rate with American Dollar, while overseas inflation, domestic interest rate , overseas interest rate they do not have significant influence toword Rupiah exchange rate with American Dollar. From the determination coefficient result (R2) show that the subject which has been researched can explain 93,11 percent toword Rupiah exchange rate while the rest 3,89 percent can be explained by other subject out of model.